PENGARUH KESEJAHTERAAN GURU TERHADAP KINERJA GURU SEKOLAH DASAR DI SD SWASTA YP HKBP 4 DAN SD NEGERI 124401 - Simanjuntak, Melvin; Aslina Tumangger; Cindi Manurung; Eryani Pakpahan; Veby Lorina Siboro; Ester Aprilia Veronika Sinaga; Maria Juwita Sinaga (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Teacher welfare is one of the problems in the field of education that occurs in Indonesia. The level of teacher welfare in Indonesia is very concerning where honorary teachers only receive Rp150,000 -Rp700,000 / month, there are several private schools demanding their rights for four months starting from January-April which have not been paid by the agency where they work, problems with the work environment, comfort, organizational climate, and others. The purpose of this study is to determine the effect of Teacher Welfare on Teacher Performance at YP HKBP 4 Private Elementary School. This study uses a correlational descriptive quantitative research type. The research subjects were 10 YP HKBP 4 Private Elementary School teachers. The research data were collected using a questionnaire, then tested for data analysis using SPSS. At YP HKBP 4 Private Elementary School, the t-value was 5.403, the t-table was 2.045, and the significance was 0.00. Meanwhile, at SD Negeri 124401, the calculated value was 2.538, the ttable was 2.120, and the significance was 0.02. Based on these results, it can be concluded that at SD Swasta YP HKBP 4 and SD Negeri 124401, it can be seen that teacher welfare has a significant effect on teacher performance.